2014
DOI: 10.1007/s13679-013-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Obesity Over the Life Span: Ecological and Genetic Highlights from Asian Countries

Abstract: Obesity is a worldwide pandemic, and the prevalence rate has doubled since the 1980s. Asian countries are also experiencing the global epidemic of obesity with its related health consequences. The prevalence of overweight and obesity are increasing at an alarming rate across all age groups in Asia. These increases are mainly attributed to rapid economic growth, which leads to socio-economic, nutrition and lifestyle transitions, resulting in a positive energy balance. In addition, fat mass and obesity-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 130 publications
1
6
0
Order By: Relevance
“…This result was consistent with previous studies that revealed A19G and G2548A were not associated with obesity related variables that evaluated, including WC, BF and metabolic parameters (Constantin et al 2010;Franek et al 2010). The complex pathogenesis of obesity was hypothesized that might involve the interaction between genetics, hormonal, environmental and lifestyles (Alfredo et al 2007;Chong et al 2014;Khor 2012;Paracchini 2005). Therefore, the prevention and management of obesity and its comorbidities are particularly challenging due to multifactorial of obesity development.…”
Section: Discussionsupporting
confidence: 90%
“…This result was consistent with previous studies that revealed A19G and G2548A were not associated with obesity related variables that evaluated, including WC, BF and metabolic parameters (Constantin et al 2010;Franek et al 2010). The complex pathogenesis of obesity was hypothesized that might involve the interaction between genetics, hormonal, environmental and lifestyles (Alfredo et al 2007;Chong et al 2014;Khor 2012;Paracchini 2005). Therefore, the prevention and management of obesity and its comorbidities are particularly challenging due to multifactorial of obesity development.…”
Section: Discussionsupporting
confidence: 90%
“…An early predisposition to accumulate excess fat has been linked with genetic and epigenetic factors, as well as features of the early food environment (Rhee et al, 2012, Chong et al, 2014, Gluckman and Hanson, 2008, McAllister et al, 2009, Lin et al, 2017). It has been previously proposed that a pathway between genetic factors and future obesity risk is mediated by appetitive traits and eating behaviours that promote greater energy intakes, in what has been referred to as the ‘behavioural susceptibility theory of obesity’ (Llewellyn and Wardle, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Restricting unhealthy food marketing to children has been identified as a cost-effective strategy for reducing the prevalence of childhood obesity (Magnus et al, 2009;Swinburn et al, 2004). Epidemiological evidence indicates that while the prevalence of overweight and obesity is lower in many developing countries across the Asia Pacific region, the rate of increase in prevalence in the previous few decades is much higher than that of developed countries (Asia Pacific Cohort Studies Collaboration, 2007;Chong et al, 2014). Yet few LMIC (and indeed developed countries) have regulations to limit children's exposure to this form of marketing.…”
Section: Introductionmentioning
confidence: 99%